Oil and gas trends and implications in Malaysia - Khalid, Abdul Rahim; Audrey, Liwan (Elsevier Ltd., 2012)
The trends of reserves, production and consumption of oil in Malaysia to meet the ever-increasing demands do not seem to show that oil and gas will be depleted soon, contrary to many reports. Malaysia’s net exporter status of oil continues to expand over time for as long as the value of exports is greater than the value of imports. Only in physical quantities of oil that Malaysia’s imports exceed exports, but this does not mean that Malaysia will be a net importer by then. Given higher prices of exports, the value of exports outweighs the value of imports. If the current reserves are extracted based on the domestic consumption trend of 1980–2010, Malaysia’s reserves will last until 2027 but based on the 1998–2010 trend, the reserves will be depleted by 2035. Malaysia has adopted a four fuel diversification strategy comprising oil, gas, coal and hydro, instead of heavily dependent on oil. Gas has a huge potential for domestic utilization as well as for exports to increase revenues. Malaysia is one of the few countries having many types of renewable energy sources. Malaysia has great potential in biomass utilization as renewable resources mostly from the existing natural forest and planned plantations.